Atividade de voo de colônias da abelha sem ferrão Plebeia aff. flavocincta em condições tropicais do litoral cearense - Barbosa, Artur Bruno da Silva (2019)
Bees are the main pollinators and are responsible for the pollination of most wild and cultivated plants by man. The present study aimed to understand the flight activity behavior of the stingless bee Plebeia aff. flavocincta in tropical conditions throughout the year and also to investigate which factors may influence in this type of behavior. The flight activities of the P. aff. flavocincta bee were recorded monthly for 5 consecutive days in four colonies kept in rational hives. The flow of bees was quantified by manual counters for 10 minutes per hour while there was natural light. The number of bees performing the flight activities was evaluated by means of an analysis of variance by the Kruskal-Wallis test, followed by the Dunn test adjusted by the Bonferroni methodology. The colonies of P. aff. flavocincta remained active throughout the year. The meteorological parameters that had significant effect on the behaviors were temperature, relative humidity and wind speed. It was possible to distinguish two periods of external activity: period 1, with more food supply in the field which there were great flowerings, and period 2, which corresponded to the transition period between the rainy and dry season, presenting few available food resources. It was observed that the external flight activity of Plebeia aff. flavocincta is not directly related to the periods of occurrence or absence of rainfall, but at the time of the year of greater and lesser availability of food resources within the flight range of the species.